The impact of Construction legislations on structural deterioration of Baghdad commercial streets - Aljumaily, Saad Kh.Mahmoud; Aljazaery, Miaad Adnan Hashem; Abed Aljabbar, Khansaa Abed Alrahman (Nahrain University College of Engineering Journal, 2017)
Construction guide lines are set in the world to achieve several goals, including the organization of city centers and suburbs, streets and sectors, to avoid chaos and indiscriminate uses of the land, and improve the appearance of urban and aesthetic of the cities, through the adaption of set of laws and regulations that regulate the relationship of institutions involved in management and between real estate owners and investors on the one hand, to promote the aesthetic character and fun to its users on the other. Commercial street in Baghdad mixed-use at the present time, are public places used by people every day, for the purposes of shopping, leisure, walking, sitting, waiting, and must be provided the maximum possible service, after It was planned to be allocated for traffic moving from one place to another, so there was a need to pay attention to it and maintained as a public realm places and favorite people. As a result, governments are seeking to reform its cities and developed through the review of controls construction, in response to the movement and the need of people to the streets safe and comfortable with densities balanced, providing comfort and beauty, safety and environmental protection and accessibility in addition to achieving the best use of the value of the land. The research focuses on studying of some local building codes of Baghdad City and its suburbs, which have contributed to the deterioration of the construction of most main streets, which is the Urban Structure and Urban have, instead of upgrading them, and these laws with regard to high buildings to the streets of the commercial and mixed use, and determine the distance of set-back and visibility of these the buildings. This will be done by addressing the standards of containment space you are working on and seeking to achieve most of the studies and research and the States to improve the Authority of the urban cities, and to study the compatibility and conflicts with the organization of local building laws. The results showed that the current local building regulations do not use these criteria despite the continuous updating of such controls, which will lead to continued deterioration of the physical suffering of the people and the continuity of use.